2011
DOI: 10.1038/ng.824
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies susceptibility loci for open angle glaucoma at TMCO1 and CDKN2B-AS1

Abstract: A genome-wide association study (GWAS) for open angle glaucoma (OAG) blindness was conducted using a discovery cohort of 590 cases with severe visual field loss and 3956 controls. Genome-wide significant associations were identified at TMCO1 (rs4656461 (G) OR=1.68, p=6.1x10 -10 ) and CDKN2B-AS1 (rs4977756 (A) OR = 1.50, p=4.7x10 -9 ). These findings were replicated in a second cohort of advanced OAG cases (rs4656461 p=0.010; rs4977756 p=0.042) and two further cohorts of less severe OAG. The study wide odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
398
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 386 publications
(424 citation statements)
references
References 31 publications
19
398
1
6
Order By: Relevance
“…A role for both TMCO1 and CDKN2B-AS1 in the retinal ganglion cell apoptosis was proposed. 126 The most recently published study regarding identification of new loci associated with POAG is the one by Porter et al 127 who identified a new POAG locus, GLC1Q, on chromosome 4 at 4q35.1-q35.2. They investigated the genetic cause of POAG in a large four-generation family with an apparent autosomal dominant mode of inheritance using genome-wide linkage analysis, but they failed to identify a mutation within the critical region in the candidate genes LRPB2BP, CYP4V2 and UFSP2.…”
Section: Wdr36 At the Glc1g Locusmentioning
confidence: 99%
“…A role for both TMCO1 and CDKN2B-AS1 in the retinal ganglion cell apoptosis was proposed. 126 The most recently published study regarding identification of new loci associated with POAG is the one by Porter et al 127 who identified a new POAG locus, GLC1Q, on chromosome 4 at 4q35.1-q35.2. They investigated the genetic cause of POAG in a large four-generation family with an apparent autosomal dominant mode of inheritance using genome-wide linkage analysis, but they failed to identify a mutation within the critical region in the candidate genes LRPB2BP, CYP4V2 and UFSP2.…”
Section: Wdr36 At the Glc1g Locusmentioning
confidence: 99%
“…Recently, several POAG susceptibility loci were identified by genome-wide association (GWA) studies [16][17][18][19][20] and were replicated in multiple ethnicities: 7q31.2 between CAV1 and CAV2, 16,21 9p21.3 with CDKN2B-AS1, 19,20,[22][23][24][25][26] 10q21.3 with ATOH7, 17,18,22,27 and 14q23.1 between SIX1 and SIX6. 17,20,22,28 One of the GWA studies demonstrated the association of POAG with six SNPs that flanked the ZP4, PLXDC2, and TMTC2 genes located at chromosome loci 1q43, 10p12.31, and 12q21.31, respectively, in a Japanese population; 29 however, these associations were not replicated in a South Indian, 30 Afro-Caribbean, 24 or Chinese 31 population.…”
Section: Introductionmentioning
confidence: 99%
“…113 TMCO1, as mentioned previously, has been suggested to be associated with POAG. 31 Van Koolwijk et al 112 also investigated the effect of the minor alleles of these genes on POAG. The minor allele of GAS7, which decreased IOP by 0.19 mm Hg, reduced the glaucoma risk (OR ¼ 0.88, 95% CI ¼ 0.78-0.98).…”
Section: Intraocular Pressure (Iop)mentioning
confidence: 99%